Cloud forensics issues and oppurtunities - Aminnezhad, Asou; Dehghantanha, Ali; Abdullah@Selimun, Mohd Taufik; Damshenas, Mohsen (Advanced Institute of Convergence Information Technology, 2013)
Cloud computing technology is a rapidly growing field of study, which relies on sharing computing resources rather than having local servers or personal devices to handle applications. Most of the growth in this field is due to transfer of the traditional model of IT services to a novel model of cloud and the ubiquity of access to electronic and digital devices. Cloud computing posed a critical risk and challenges to digital investigators, but provides plenty of opportunities to investigators for improving the digital forensics. Moreover, cloud service providers and customers have yet to establish adequate forensic capabilities that could support investigations of criminal activities in the cloud. Notwithstanding the cloud presents some promising technical and economic benefits, users still resist to use cloud mainly due to security issues because it poses a challenge in doing cloud forensic investigations. Regarding this some research has been done, which propose solutions in doing forensic investigation. In this review paper, we take the first step towards reviewing the cloud forensics works that have been done by other researchers, and then do some discussion and analysis based on our findings to consider the opportunities and challenges confront the cloud forensics based on our findings.